2020
DOI: 10.3390/rs12040731
|View full text |Cite
|
Sign up to set email alerts
|

Lunar Regolith Temperature Variation in the Rümker Region Based on the Real-Time Illumination

Abstract: Chang’E-5 will be China’s first sample−return mission. The proposed landing site is at the late-Eratosthenian-aged Rümker region of the lunar nearside. During this mission, a driller will be sunk into the lunar regolith to collect samples from depths up to two meters. This mission provides an ideal opportunity to investigate the lunar regolith temperature variation, which is important to the drilling program. This study focuses on the temperature variation of lunar regolith, especially the subsurface temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…With these parameter constraints, it was found that the observed H-content depth profiles of the CE-5 grains can be preserved for 10 to 10 5 y after burial to a few centimeters below the surface ( Fig. 3 A and B and SI Appendix, Table S6 ), where the maximum temperature is in the range of 360 to 300 K ( 49 ). By contrast, the Apollo soils, situated at a higher temperature by ~20 K relative to the CE-5 soils, could have experienced significant diffusion loss of the SW-derived hydrogen, whereas the soils in the polar regions (~300 K at a latitude of 75˚) could be almost completely preserved from diffusion loss.…”
Section: Discussionmentioning
confidence: 99%
“…With these parameter constraints, it was found that the observed H-content depth profiles of the CE-5 grains can be preserved for 10 to 10 5 y after burial to a few centimeters below the surface ( Fig. 3 A and B and SI Appendix, Table S6 ), where the maximum temperature is in the range of 360 to 300 K ( 49 ). By contrast, the Apollo soils, situated at a higher temperature by ~20 K relative to the CE-5 soils, could have experienced significant diffusion loss of the SW-derived hydrogen, whereas the soils in the polar regions (~300 K at a latitude of 75˚) could be almost completely preserved from diffusion loss.…”
Section: Discussionmentioning
confidence: 99%
“…The mean TB in Em2 indicates a similar behavior to Im2 as shown in Figure 10. It should be mentioned that the mean TB in Em2 is slightly higher than Im2 both in the daytime and at night, which probably could be explained by 1) the effective solar illumination in Em2 is higher than Im2 according to the numerical simulation [46,58,59], which makes the physical temperature in Em2 be higher than Im2; 2) the linear interpolation method to generate TB products (Figures 3-6) will smooth the difference of the nearby regions (the relatively higher TB surrounding Em2 at noon will enhance the difference of the TB between Im2 and Em2; the relatively lower TB surrounding Em2 at night will decrease the difference of the TB between Im2 and Em2). The change of the mean TB with time is nearly identical between Em2 and Im2 ( Figure 10), suggesting similar thermophysical feature of the mare deposits.…”
Section: New Views Of Geologic Unitsmentioning
confidence: 97%
“…Considering the depths of drill core samples studied here, our data demonstrate that more than half of the lunar soils could preserve SW‐derived water for hundreds of millions of years if buried at depth. The preservation of water most likely benefits from the relatively low temperature below the lunar surface due to the low thermal conductivity of lunar regolith (∼240 K for depth >0.5 m vs. a maximum temperature of ∼360 K for the surface, Williams et al., 2017; Zhong et al., 2020).…”
Section: Discussionmentioning
confidence: 99%